DEVELOPING READING BOOK THROUGH EXTENSIVE READING ‘UNSKILLED JOBS’ - Fergina, Ana; Yuline, Yuline; Putri, Amallia (Academy of Education Journal, 2023)
Extensive reading material is reading material that can help students improve their reading skills in speed and increase vocabulary. Some reading materials discuss professional occupations such as doctors and teachers. However, not many introduce unskilled work, even though this work is an existing job and has even existed for generations. This research on the development of extensive reading materials aims to produce a book product on the types of untrained/academic work. This book introduces these types of unskilled jobs in West Kalimantan. As reading material, this book is an alternative reading in English with vocabulary that are easy to understand in the local context. This book is used as supplementary reading material for Tanjungpura University’s students.